2020
DOI: 10.3390/jcm9030814
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Implementation of Pharmacogenomic Panel-Testing in Primary Care in the Netherlands Utilizing a Theoretical Framework

Abstract: Despite overcoming many implementation barriers, pharmacogenomic (PGx) panel-testing is not routine practice in the Netherlands. Therefore, we aim to study pharmacists' perceived enablers and barriers for PGx panel-testing among pharmacists participating in a PGx implementation study. Here, pharmacists identify primary care patients, initiating one of 39 drugs with a Dutch Pharmacogenetic Working Group (DPWG) recommendation and subsequently utilizing the results of a 12 gene PGx panel test to guide dose and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…In agreement with the literature, our results show that current practical experience with PGx is limited, even though DPWG guidelines have been available nationwide since 2006 [ 2 , 4 , 7 ]. A lack of knowledge and training among healthcare practitioners has previously been reported as a barrier to PGx implementation [ 1 , 8 , 9 , 10 , 12 , 13 ]. The community and hospital pharmacists in our study reported wanting more education about PGx for themselves and pharmacy staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with the literature, our results show that current practical experience with PGx is limited, even though DPWG guidelines have been available nationwide since 2006 [ 2 , 4 , 7 ]. A lack of knowledge and training among healthcare practitioners has previously been reported as a barrier to PGx implementation [ 1 , 8 , 9 , 10 , 12 , 13 ]. The community and hospital pharmacists in our study reported wanting more education about PGx for themselves and pharmacy staff.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports that recognition of the clinical utility of PGx is a facilitator for implementation and that disbelief is a barrier [ 8 , 9 , 10 , 12 , 13 ]. In our study, patients were positive about PGx, including its expected clinical utility, regardless of the occurrence of DGIs during their treatment, whereas healthcare practitioners were generally positive about the clinical utility, although some did not feel ready to apply it in daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when genetic testing is reimbursed or incorporated into biobank or neonatal screening programs, considerable economies of scale could be leveraged that reduce test costs well below $40. 34,35 We furthermore conducted a sensitivity analysis of our recommendations to test costs, in which we assumed the highest HLA genotyping costs found in the literature ($141; results provided in Table S9). As expected, increasing the genotyping costs lowered the incremental cost thresholds.…”
Section: Articlementioning
confidence: 99%
“…Not only does PGx testing promise to improve efficacy and safety outcomes for patients, it could also lead to overall savings in health care costs due to more efficient patient management strategies. Particularly preemptive PGx testing with multigene panels may be a promising approach for the identification of clinically relevant variants [ 8 ]. If they are used in a high number of subjects, costs of PGx testing may decrease considerably and therefore have a major impact on weighing costs vs. benefits.…”
Section: Introductionmentioning
confidence: 99%